2017
DOI: 10.1080/13538322.2017.1294410
|View full text |Cite
|
Sign up to set email alerts
|

Scenarios of quality assurance of stakeholder relationships in Finnish higher education institutions

Abstract: Although the role and significance of the external stakeholders of higher education institutions has grown in recent years, quality assurance of stakeholder relationships remains a new phenomenon in the management practices of higher education institutions and in higher education research. Based on interviews and expert panel data, this article analyses the internal and external stakeholders' perceptions of scenarios of the quality assurance of stakeholder relationships in Finnish higher education institutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 31 publications
3
16
0
1
Order By: Relevance
“…In contrast to previous research conducted by Marasabessy (2008), Abroza (2015), and Asy'ari (2013), which found evidence that quality assurance affects organizational performance, the findings of this study prove the opposite relationship. Meanwhile, related to the significant relationship between organizational culture and organizational performance both directly and indirectly mediated by quality assurance, this study justifies several previous theories which show that organizational culture is an important predictor of the creation of systems that can encourage high organizational performance (López et al, 2015;Lyytinen et al, 2017;Martin, 2016;Mourad, 2017;Prakash, 2018;Sadler, 2017;Santos and Dias, 2017;Tam, 2001;Yingqiang and Yongjian, 2016).…”
Section: Organizational Culture Quality Assurance and Organizationasupporting
confidence: 85%
See 2 more Smart Citations
“…In contrast to previous research conducted by Marasabessy (2008), Abroza (2015), and Asy'ari (2013), which found evidence that quality assurance affects organizational performance, the findings of this study prove the opposite relationship. Meanwhile, related to the significant relationship between organizational culture and organizational performance both directly and indirectly mediated by quality assurance, this study justifies several previous theories which show that organizational culture is an important predictor of the creation of systems that can encourage high organizational performance (López et al, 2015;Lyytinen et al, 2017;Martin, 2016;Mourad, 2017;Prakash, 2018;Sadler, 2017;Santos and Dias, 2017;Tam, 2001;Yingqiang and Yongjian, 2016).…”
Section: Organizational Culture Quality Assurance and Organizationasupporting
confidence: 85%
“…Recent literature reviews have explored themes that drive organizational performance, especially HEIs performance such as effective leadership (Alonderiene and Majauskaite, 2016;Awuzie and Emuze, 2017;Spendlove, 2007), organizational culture (Haryono and Arafat, 2017;Ibrahim et al, 2018;Imam et al, 2013), and quality assurance (López et al, 2015;Lyytinen et al, 2017;Martin, 2016;Mourad, 2017;Prakash, 2018;Sadler, 2017;Santos and Dias, 2017;Tam, 2001;Yingqiang and Yongjian, 2016). However, some literature fails to prove that leadership has an influence on performance (Sihombing et al, 2018) and organizational culture (Shiva and Suar, 2012).…”
Section: Literature Review Transformational Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on external stakeholders and their involvement in higher education, especially with regard to governance of higher education institutions and to quality assurance (Beerkens & Udam, 2017;Leisyte & Westerheijden, 2014;Magalhães, Veiga, & Amaral, 2018;Musiał, 2010;Pinheiro, 2015;Rosa & Teixeira, 2014), has often raised concerns about the involvement of external stakeholders in what are mainly seen as internal higher education matters. In fact, there have been calls for quality assurance for stakeholder relationships (Lyytinen et al, 2017), while others have labelled external stakeholders 'Trojan horses' or 'imaginary friends' (Magalhães et al, 2018;Rosa & Teixeira, 2014). However, the voices of external stakeholders are rarely heard in this stream of literature.…”
Section: Introductionmentioning
confidence: 99%
“…The salience model, as a typology of stakeholders, offers three attributes to describe the stakeholder-manager relationship (Mitchell et al, 1997). This model is also used in the context of higher education for discussing stakeholder-manager relationships (Lyytinen, Kohtamäki, Kivistö, Pekkola, & Hölttä, 2017;Powell & Walsh, 2018). The challenge of using this model in this study is to adapt it for the research purpose.…”
Section: The Salience Model For Stakeholdersmentioning
confidence: 99%